Language familiarity influences own‐race face recognition in 9‐ and 12‐month‐old infants. (14th May 2021) - Hillairet de Boisferon, Anne; Kubicek, Claudia; Gervain, Judit; Schwarzer, Gudrun; Loevenbruck, Hélène; Vilain, Anne; Fort, Mathilde; Méary, David; Pascalis, Olivier
Abstract: During their first year, infants attune to the faces and language(s) that are frequent in their environment. The present study investigates the impact of language familiarity on how French‐learning 9‐ and 12‐month‐olds recognize own‐race faces. In Experiment 1, infants were familiarized with the talking face of a Caucasian bilingual German‐French speaker reciting a nursery rhyme in French (native condition) or in German (non‐native condition). In the test phase, infants' face recognition was tested by presenting a picture of the speaker's face they were familiarized with, side by side with a novel face. At 9 and 12 months, neither infants in the native condition nor the ones in the non‐native condition clearly recognized the speaker's face. In Experiment 2, we familiarized infants with the still picture of the speaker's face, along with the auditory speech stream. This time, both 9‐ and 12‐month‐olds recognized the face of the speaker they had been familiarized with, but only if she spoke in their native language. This study shows that at least from 9 months of age, language modulates the way faces are recognized.